Marketing Strategy of 3M Sandpaper - kusumoanggo, Prabantoko; Hudrasyah, Herry (The Indonesian Journal of Business Administration, 2013)
Business situation nowadays has undergone many changes as well as the competition which is getting fierce and tougher. The strong pressure in domestic competition has changed the nature of the economy led to a change in the way of operating for industrial enterprises. Facing this situation the company should be able to survive and win the competition by doing a strategy-oriented growth in the future. A multi level company in Indonesia facing stagnant sales problem of sandpaper product. Sales close to zero, but the quality of the product is actually great and promising. And now how to increase shares in sandpaper market with this situation. By doing market research and internal-external analysis, the root cause of the stagnant sales can be known and be solved immediately. By performing a comprehensive marketing strategy using the STP - Marketing Mix, Brand Awareness, Competition â€“ Customer Analysis, 5C (Market Analysis) and Porter Five Forces as a tool to analyze the problem and determine the right marketing strategy that is able to deliver the changes and evaluate performance in creating a value in days to come through improved performance of the activities that carry out the proposed marketing strategy. The implementation of those marketing strategy starts from the rebranding, the increased activities of promotion and improvement of distribution channels as well as the market expansion, so that leading to a change towards the improvement of the company itself.Â Key words: Rebranding, marketing strategy, promotion, and market expansion.